A Proposed Biseni Orthography (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Biseni is a dialect of the Ijọ language, and is spoken in the Northern extreme of the Taylor Creek in Yenagoa Local Government Area of Bayelsa State, Nigeria. The dialect is significantly divergent with other Ijọ dialects, except for Okordia and Oruma (also called Yibama) with which it shares significant intelligibility levels; 80% for Biseni and Okordia, 66% for Biseni and Oruma. Biseni has no existing orthography, resulting in different and inconsistent spelling/writing patterns for constructions, words and even names in the dialect. This paper presents a proposed Orthography for Biseni and discusses issues related thereof, as part of efforts at developing and bequeathing a consistent written form for it.